2021
DOI: 10.1007/s11625-021-00967-2
|View full text |Cite|
|
Sign up to set email alerts
|

Land systems’ asymmetries across transnational ecoregions in South America

Abstract: The landscape configuration of socio-ecological land systems results from the interaction between the environmental conditions (relatively homogeneous within ecoregions) and country-level management and land-use decisions. However, social, land-use and sustainability research disciplines often study each independently. We used Euclidean distance analyses of five indicators of land systems functioning to explore the geographical patterns of across-border human-induced asymmetries in transnational ecoregions of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
0
4
0
1
Order By: Relevance
“…For example, the Mexico-U.S., China-Myanmar, Bangladesh-India, and some Asian borders experience high pressure to prevent illegal wildlife trade 17 , 43 which were also identified as transboundary invasion hotspots in our study. We need to pay close attention to areas undergoing rapid anthropogenic disturbances across the African, American and Asia-Pacific tropics, such as Brazil-Paraguay, Colombia-Venezuela, and Indonesian Borneo 44 , 45 , which were all identified as transboundary invasion hotspots (Figs. 1 – 3 ; Supplementary Table 1 , Supplementary Data 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Mexico-U.S., China-Myanmar, Bangladesh-India, and some Asian borders experience high pressure to prevent illegal wildlife trade 17 , 43 which were also identified as transboundary invasion hotspots in our study. We need to pay close attention to areas undergoing rapid anthropogenic disturbances across the African, American and Asia-Pacific tropics, such as Brazil-Paraguay, Colombia-Venezuela, and Indonesian Borneo 44 , 45 , which were all identified as transboundary invasion hotspots (Figs. 1 – 3 ; Supplementary Table 1 , Supplementary Data 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human intervention at large scales creates new scenarios with novel ecological systems (i.e. Anthromes) (Ellis, 2011; Piquer‐Rodríguez et al, 2021) that may present different biogeographic patterns to those observed in natural habitats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, even though two countries share a similar ecosystem (e.g., tropical lowland forest), the values assigned to this ecosystem can vary greatly depending on a country's development priorities and its capacity to mobilize resources. Neighboring countries may favor different land use decisions, which can result in landscape discontinuities with major ecological consequences (Dallimer and Strange 2015;Piquer Rodríguez et al 2021). A major feature of the Anthropocene is that humans are a major driver of most ecological processes (e.g., nitrogen and carbon cycles, energy balance).…”
Section: I�����������mentioning
confidence: 99%
“…L��� ��� ����������� ������ ������������� ������� ₆₆₇ countries have more productive agriculture lands in other regions (Piquer-Rodríguez et al 2021).…”
Section: ₆₆₆ Hr G��� �� ��unclassified
See 1 more Smart Citation